Analisis Strategi Promosi dengan Memanfaatkan Media Sosial dalam Meningkatkan Volume Penjualan di Pasar Ya’ahowu Kota Gunungsitoli (Lembaga Pengembangan Kinerja Dosen, 2025)
This research is entitled Analysis of Promotion Strategies Utilizing Social Media to Increase Sales Volume at Ya’ahowu Market in Gunungsitoli City. The objectives of this study are to identify the promotion strategies used by business actors through social media, to explore the challenges they face, and to discover the solutions or efforts made to overcome these challenges. This study employs a qualitative approach using interviews with business owners at Ya’ahowu Market. The findings indicate that most business actors use social media platforms such as Facebook, WhatsApp, and Instagram to promote their products due to ease of use, wide reach, and low cost. However, the main challenges encountered include limited technological knowledge, poor internet connectivity, and low skills in creating engaging content. To address these issues, business actors take independent learning initiatives, attend digital marketing training, and collaborate with others, such as young people or family members who are more tech-savvy. The study recommends that business actors continuously improve their digital literacy, and that local government support digital promotion training for MSMEs to sustainably increase sales volume.